2020
DOI: 10.2147/ott.s259232
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00680 Promotes the Progression of Non-Small Cell Lung Cancer and Functions as a Sponge of miR-410-3p to Enhance HMGB1 Expression</p>

Abstract: Purpose: LINC00680 was reported to be involved in various cancers through multiple mechanisms. Therefore, we intended to investigate its role in the progression of non-small cell lung cancer (NSCLC). Materials and Methods: Firstly, quantitative real-time polymerase chain reaction (qRT-PCR) was used to test LINC00680 in NSCLC tissue and cell lines. Subsequently, A549 and H1299 cells were transfected with LINC00680 overexpressing plasmids and their proliferation and colony formation and apoptosis was tested by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Several studies revealed the function of LINC00680 in cancer, including promoting malignancy in glioblastoma [19], predicting the clinical outcome and survival of patients with sarcoma [18] and promoting the progression of non-small cell cancer [22]. Our work con rmed a new role of LINC00680 in breast cancer, breast cancer cells with docetaxel resistance shown increasing expression of both LINC00680 and CDKL5 (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Several studies revealed the function of LINC00680 in cancer, including promoting malignancy in glioblastoma [19], predicting the clinical outcome and survival of patients with sarcoma [18] and promoting the progression of non-small cell cancer [22]. Our work con rmed a new role of LINC00680 in breast cancer, breast cancer cells with docetaxel resistance shown increasing expression of both LINC00680 and CDKL5 (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…So the investigation of the role of lncRNAs in breast cancer could help with the understanding of chemotherapy resistance and provide the novel therapeutic strategy. LINC00680 is rstly reported as a protective biomarker and an independent prognostic indicator of softtissue sarcoma [18], then it was reported to promote the progression of non-small cell lung cancer and glioblastoma cells [19,20]. Nevertheless, the expression pattern, biological function and underlying mechanism of LINC00680 in breast cancer progression and docetaxel resistance are scarcely unresearched.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that LINC00680 is upregulated in NSCLC and is closely associated with malignancy and the poor prognosis of NSCLC patients. LINC00680 enhanced the growth of NSCLC cells in mice, increased proliferation and colony formation, and suppressed apoptosis of H1299 and A549 cells, by functioning as a sponge of miR-410-3p to improve HMGB1 expression [ 106 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Using biologically-replicated drop-out screens, 77 lncRNAs were identified as necessary for proliferation of A549 cells. These include known NSCLC lncRNAs, such as LINC00324 (42), ZFAS1 (43), MIR31HG (44), SBF2-AS1 (45), LINC00680 (46) and LINC00511 (47), that was also found in H460. In addition, lncRNAs identified in other cancer types include LUNAR1 (48), HEIH (49) and LINC00910 (50) (Figure 2e).…”
Section: Multi-phenotype Mapping Of Nsclc Lncrnasmentioning
confidence: 90%